Linguistic ideologies, bilingualism, and Spanish as a heritage language in Europe - Álvarez Mella, Héctor; Moreno Fernández, Francisco; Elizondo Romo, Mariel (HCIAS working papers on Ibero-America, 2025)
The article explores the different discourses about bilingualism and heritage languages produced by early bilingual education initiatives. More concretely, it analyzes the recurring beliefs, ideas, and conceptualizations that circulate about bilingualism and Spanish as a heritage language within bilingual education spaces of different European countries. The empirical analyses addresses presented three research questions: 1) What are the main ideologies about bilingualism and heritage languages circulating in the discourses of these education initiatives? 2) What are their main discursive expressions? And 3) how do they discursively interrelate? The results show how the early bilingual education spaces are framed by a purist idea of bilingualism, a cosmopolitan image of bilingual education, and a vision of Spanish that emphasizes the culture and identity dimensions of heritage languages.
Gesehen am 03.02.2025